A real application of the theory of constraints to Supply chain management in Brazil - Reinaldo Fagundes Dos Santos; Fernando Augusto Silva Marins; João Murta Alves; Artur Henrique Moellmann (Brazilian Journal of Operations & Production Management, 2011)
This paper presents how the concepts of Theory of Constraints (TOC), Vendor Managed Inventory (VMI) and Business-to-Business (B2B) tools can be applied to Supply Chain Management (SCM) in order to improve the global supply chain performance. First of all, the TOC concepts and the SCM dilemma, according to TOC thinking, are to be summarized. After that, an alternative TOC approach to SCM will be described, which uses VMI & B2B to minimize the bullwhip effect and inventory levels, therefore as a SC performance improvement. The proposed approach is illustrated by means of a real case study in a Brazilian middle size company, related to the small appliances production.